THE REPRESENTATION OF THE SPIONAGE ISSUE IN THE JAKARTA POST AND ABC NEWS USING TEXTUAL METAFUNCTION - Lucky Rahayu Nurjamin (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
This study is aimed at investigating the representation of two different newspapers, The Jakarta Post and ABC news, as seen from textual metafunction concerning the issue about the spionage of Australia-Indonesia. Qualitative in terms of document analysis related to discourse analysis was employed in this study. This study used functional grammar framework due to reveal the representation appeared in the media. It was found that both articles favored in representing the issue. The Jakarta Post consists of 60% as topical theme and 40% as textual theme. Whereas, ABC news consists of 62.26% topical, 35.84% textual, and 1.88% as interpersonal themes. This means that both favored the representation of the issue with a signal of what is to be understood as the framework as what the readers want to assume (Mc Charty,1991). The relationship of the theme to the rest of the sentence is viewed as part of communicative dynamism, that is the assessment of the extent to which each element contributes to developing the communication.